Students’ Perceptions of Flipped Classroom in English Teaching at SMAN 3 Sinjai - Sari, Ira Puspita; Noni, Nurdin; Aeni, Nur (Journal of Excellence in English Language Education, 2025)
This study explored students’ perceptions of the flipped classroom model in English teaching at SMAN 3 Sinjai. The flipped classroom, an innovative teaching approach, encourages students to study learning materials before class, enabling active participation during in-class sessions. Using a qualitative descriptive method, data were gathered through semi-structured interviews with 12 students and classroom observations. Findings revealed that students generally had positive perceptions of the flipped classroom. They appreciated its flexibility, prior access to materials, and opportunities for interactive discussions. However, challenges such as technological barriers, lack of direct support at home, and varying levels of student motivation were also noted. The study highlights the need for strategies to address these challenges and maximize the benefits of the flipped classroom in enhancing English learning outcomes.